N- and O-Glycosylation Pathways in the Microalgae Polyphyletic Group - Mathieu-Rivet, Elodie; Mati-Baouche, Narimane; Walet-Balieu, Marie-Laure; Lerouge, Patrice; Bardor, Muriel (Frontiers in Plant Science, 2020)
The term microalga refers to various unicellular and photosynthetic organisms representing a polyphyletic group. It gathers numerous species, which can be found in cyanobacteria (i.e. Arthrospira) as well as in distinct eukaryotic groups, such as Chlorophytes (i.e. Chlamydomonas or Chlorella) and Heterokonts (i.e. diatoms). This phylogenetic diversity results in an extraordinary variety of metabolic pathways, offering large possibilities for the production of natural compounds like pigments or lipids that can explain the ever-growing interest of industrials for these organisms since the middle of the last century. More recently, several species have received particular attention as biofactories for the production of recombinant proteins. Indeed, microalgae are easy to grow, safe and cheap making them attractive alternatives as heterologous expression systems. In this last scope of applications, the glycosylation capacity of these organisms must be considered as this post-translational modification of proteins impacts their structural and biological features. Although these mechanisms are well known in various Eukaryotes like mammals, plants or insects, only a few studies have been undertaken for the investigation of the protein glycosylation in microalgae. Recently, significant progresses have been made especially regarding protein N-glycosylation, while O-glycosylation remain poorly known. This review aims at summarizing the recent data in order to assess the state-of-the art knowledge in glycosylation processing in microalgae.